Respostas
respondido por:
0
29) Cubo da diferença: (2a-1)³ = (2a)³ - 3*(2a)²*1 + 3*2a*1²-1³ =
8a³- 12a+6a-1 = 8a³-6a-1
30) Soma pela diferença: (2a+1)(2a-1) = (2a)² - 1²
31) Quadrado da soma: (2a+2)²= (2a)² + 2*2a*2 + 2² = 4a² + 8a + 4
32) Quadrado da diferença: (2a-2)²= (2a)² - 2*2a*2 + 2² = 4a² - 8a + 4
33) Cubo da soma: (2a+2)³ = (2a)³ + 3*(2a)²*2 + 3*2a*2² + 2³= 8a³ + 12a²+24a + 8
34) Cubo da diferença: (2a-2)³ = (2a)³ - 3*(2a)²*2 + 3*2a*2² - 2³ = 8a³ - 24a² + 24a - 8
35) Soma pela diferença:(2a+2)(2a-2) = (2a)²- 1²
36) Quadrado da soma: (3a+1)² = (3a)² + 2*3a*1 + 1² = 9a²+6a+1
37) Quadrado da diferença: (3a-1)²= (3a)² - 2*3a*1 + 1² = 9a² - 6a + 1
38) Cubo da soma: (3a+1)³= (3a)³ + 3*(3a)²*1 + 3*3a*1² + 1³ = 27a³ +27a² + 9a+ 1
39) ??
8a³- 12a+6a-1 = 8a³-6a-1
30) Soma pela diferença: (2a+1)(2a-1) = (2a)² - 1²
31) Quadrado da soma: (2a+2)²= (2a)² + 2*2a*2 + 2² = 4a² + 8a + 4
32) Quadrado da diferença: (2a-2)²= (2a)² - 2*2a*2 + 2² = 4a² - 8a + 4
33) Cubo da soma: (2a+2)³ = (2a)³ + 3*(2a)²*2 + 3*2a*2² + 2³= 8a³ + 12a²+24a + 8
34) Cubo da diferença: (2a-2)³ = (2a)³ - 3*(2a)²*2 + 3*2a*2² - 2³ = 8a³ - 24a² + 24a - 8
35) Soma pela diferença:(2a+2)(2a-2) = (2a)²- 1²
36) Quadrado da soma: (3a+1)² = (3a)² + 2*3a*1 + 1² = 9a²+6a+1
37) Quadrado da diferença: (3a-1)²= (3a)² - 2*3a*1 + 1² = 9a² - 6a + 1
38) Cubo da soma: (3a+1)³= (3a)³ + 3*(3a)²*1 + 3*3a*1² + 1³ = 27a³ +27a² + 9a+ 1
39) ??
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás